REPRODUKSI IKAN NILA (Oreochromis nilotkm) SELEKSI DAN NON SELEKSI DENGAN PEMIJAHAN BUATAN: KARAKTERINDUK, TELUR, EMBRIODAN BENIH [Reproduction of selected and non selected nile tilapia (Oreochromis niloticm) with artificial induced breeding: character of broodstoek, egg, embryo, and larvae] - Yohanna R. Widyastuti; Jojo Subagja; Rudhy Gustiano (Jurnal Iktiologi Indonesia, 2008)
Selection program is one alternative to control and improve growth performance. It is well known that decreasing growth rate has a correlation to the early maturation of the brood stocks. Objective of the present study was to elaborate the information of bioreproduction parameters of selected tilapia brood stocks coming from selective breeding on the growth improvement. Three groups of brood stock were used in this study defining as the first generation of selected brood stock (01) and the second generation (02) and farmer’s tilapia (M). Each group of brood stock has 5 pair brood stocks as replications. Hormone injection was given for artificial spawning. Eggs were then incubated in the jars equipped with recirculation system. Larvae were transferred to aquaria for growth observation. Results showed that artificial spawning could be done on tilapia using hCG injection as priming prior to ovaprim. Although there were no significantly different (P > 0.05) in egg diameters, the eggs of selected brood stock were still slightly bigger than non selected brood stock. Larvae of the second generation of selected brood stock has better growth rate than the first generation and non-selected one.